Pengaruh Penambahan Tepung Kacang Kedelai (Gycine Max.L) pada Pembuatan Bakso Jamur Tiram terhadap Kualitas Fisik dan Daya Terima Konsumen - Alannys, Mauleen (Advances In Social Humanities Research, 2024)
This research is an experimental study that aims to find out how to make mushroom meatballs with the addition of soybean flour. This type of research is quantitative research with experimental methods. The data analysis techniques used are the Anova test and the Friedman test and further tests using the Tuckey test. In Indonesia, soybeans are a strategic commodity because they are one of the most important crops after rice and corn. Indonesian people like to consume processed soybean products, for several reasons, namely the price is relatively cheap and the nutrition is high. One process that can improve quality and storage is making flour. Making soybean flour involves washing the soybeans using clean, running water, then the process of soaking, boiling, draining the soybeans, then oven, grinding, and finally sieving. The process of making oyster mushroom meatballs with the addition of soy flour includes weighing all the ingredients, mixing and molding, boiling, and packaging. In the Organoleptic test, the results of the researcher's acceptance of the preferred quality of soy flour oyster mushroom meatballs were with the addition of 5% soy flour with an average value of the outer color of 4.2, the inner color of 4.10, texture of 3.97, elasticity of 4.07, aroma 4.2, taste 4.33, and shape 4.2. From the ANOVA test in terms of color, aroma, texture, taste, overall, it shows that there is no significant effect.